CULTURAL COLLABORATION STRATEGY AND DIGITAL CONSISTENCY - Fitriyah, Halimatul; Prajawati, Maretha Ika; S, Basir (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
This study aims to examine cultural collaboration strategies and digital consistency in the management of MSMEs based on local creativity, with a case study on Kedaily Coffee in Malang City. Using a descriptive qualitative approach and case study methods, data were obtained through direct observation, semi-structural interviews, and visual documentation. The results of the study show that Kedaily Coffee has succeeded in integrating batik cultural activities with the coffee experience as a differentiation strategy. In addition, the use of coffee skin waste (cascara) as an innovative beverage strengthens the sustainability value of the product. Digital strategies carried out through social media and delivery services are still inconsistent, so it needs to be strengthened in terms of content and digital management. Collaboration with local batik galleries opens up new market segmentation opportunities and supports cultural preservation. This study concludes that the synergy between cultural values and digital strategies is a potential approach in increasing the competitiveness of MSMEs in the creative economy era.